Does Access to Formal Finance Matter for Welfare and Inequality? Micro Level Evidence from Nigeria. Issue 9 (2nd September 2018) - Dimova, Ralitza; Adebowale, Olabimtan
Abstract: Using a treatment effects model, decomposition techniques and representative household data from Nigeria, we study the welfare and inequality implications of access to formal finance. While improving household welfare, formal access to finance increases inter-household inequalities, despite ameliorating the inequality enhancing effect of urban residence and enhancing the inequality ameliorating effect of greater educational attainment. The positive effect of access to formal finance on inequality is smaller than the effect of unobserved household characteristics, indicating that welfare and equality enhancing strategies should follow a holistic approach as opposed to one focusing on one isolated policy variable at a time.